STRENGTHENING THE REGULATION OF EDUCATION SERVICES FOR FAITH IN GOD ALMIGHTY - ceprudin ceprudin (Universitas 17 Agustus 1945 Semarang, 2021)
This study aims to strengthen educational services for followers of Faith in God Almighty. Strengthening education services for religious groups is an effort to equalize the right to education for all citizens. Equalization of education services is a mandate of the Constitution 1945 of the Republic of Indonesia, emphasizing that every citizen has the right to education and teaching. Based on data from the Directorate General of Population and Civil Registration (Dukcapil) of the Ministry of Home Affairs (Mendagri), until June 2021, the population of Indonesia who adheres to the Faith is 102,508 people. This amount is equivalent to 0.04 percent of the total population of Indonesia, which reaches 272.23 million people. Still, 6.35 thousand people in Central Java adhered to the Faith in the same year, equivalent to 0.02% of 37.23 million people. This study analyzes the facts of discrimination in educational services experienced by adherents of the Faith. In this research process, the type of juridical-empirical research is used. This type of research examines legal materials as well as factual data in the community. Based on the provisional facts presented, the author hypothesizes that discrimination in educational services experienced by adherents of the Faith has existed for a long time. Since independence, followers of the Faith have not received education services equivalent to devotees of the six-state religions. Before the issuance of Permendikbud No 27/2016, there were cases of refusal to register for school, not up a grade, being forced to take religious lessons. Some were forced to choose one religion to take the national exam. After the issuance of the Minister of Education and Culture, adherents of the Faith still experience various obstacles in obtaining educational services. The availability of teachers (penyuluh) and the column of Faith in online report cards (e-report) is still a problem in educational services for Faith followers. It is necessary to strengthen regulations and implementation so that the fundamental rights of education mandated by the constitution are also felt for Faith believer groups in Indonesia.